WOMEN SELF-HELP GROUPS AS VEHICLES OF SOCIAL ENTREPRENEURSHIP: A PATHWAY TO EMPOWERING MARGINALIZED WOMEN - Mamatha .N .R; Cirappa .I .B (International Journal of Research -GRANTHAALAYAH, 2025)
The empowerment of marginalized women is increasingly recognized as a critical dimension of sustainable development, particularly in contexts where socio-economic and cultural barriers restrict their access to education, employment, credit, and decision-making. Social entrepreneurship has emerged as a viable strategy to address these challenges, with microfinance-led Self-Help Groups (SHGs) proving especially effective. This study, examines the role of SHGs as grassroots vehicles of social entrepreneurship that combine financial inclusion with social change. Findings highlight that SHG-based microfinance fosters multidimensional empowerment—economic (income generation and financial independence), social (mobility, decision-making, and community participation), and psychological (self-confidence, autonomy, and agency). Evidence from initiatives such as Grameen Bank, SEWA, and Kudumbashree demonstrates how SHGs evolve into social enterprises that enhance household resilience, promote entrepreneurship, and strengthen community solidarity. However, persistent challenges such as patriarchal norms, financial illiteracy, institutional inadequacies, and mission drift limit their transformative potential. The study argues that empowerment through SHGs is not automatic but contingent upon enabling ecosystems, including gender-sensitive frameworks, capacity-building interventions, and supportive policy environments. It concludes that women-led SHGs, when integrated with education, digital literacy, health, and legal awareness, can move beyond financial tools to become engines of social transformation. Thus, SHGs provide a pathway to inclusive development by repositioning marginalized women as leaders and active agents of change.